Qualitative Study of Managerial Communication Style On The Formation of Employee Motivation and Attitude - Launa; Bambang Mudjiyanto; Fit Yanuar; Nursyamsi; Hafzotillah (Jurnal Cakrawala Akademika, 2025)
This study aims to examine the effect of managerial communication style on employee motivation and attitude. The sources of the study are extracted from previous research results. In the analysis, this study uses the concept of interpersonal communication, the concept of organizational communication, social exchange theory, and organizational support theory, using the Literature Review Study (LRS) method. The results of the study: an open and transparent communication style is able to trigger work motivation, strengthen self-confidence, and build positive attitudes of employees towards the company. In contrast, authoritarian (non-communicative) communication styles tend to reduce work motivation and create permissive attitudes of employees towards the company. This finding confirms the importance of communication management in shaping a communicative, responsive, and participative work atmosphere to improve employee motivation and performance. Company leaders and managers must develop effective communication styles to optimize organizational goals.